Designing A Model of the Dimensions of the Telecommunications Corporate Brand with Product Features in Mobile Phones. - Ahmad Tarfawi; Seyed Reza Seyed Javadin; Hassan Qolipour (Kurdish Studies, 2023)
Today, corporate brand dimensions are very important as a key concept for brand development and success in the market of Iraqi mobile phone companies. This research aims to design a model of corporate brand dimensions and related product features in mobile phone companies. According to its goals, the present research is of the developmental research type and in terms of the process of doing the work, it is of the exploratory type. The method of data collection in this research is both field and library methods. The current research method is qualitative. The qualitative approach in this research is inductive, and it is done using the Glazer-type foundation data method. Semi-structured interviews were used to collect data in the qualitative part of this research. Based on the results after performing three stages of open coding, selective coding, and theoretical coding, a total of 5 categories, 26 concepts, and 71 final codes were obtained, which showed that effective brand dimensions include corporate brand dimensions, product features, purchase decision, brand loyalty and environmental factors" in connection with the development of brand dimensions with product features have the role of an effective factor on the purchase decision and loyalty of mobile phone customers. In the end, the conceptual model and the corresponding theory are presented.